IDEAS OF POLYCULTURALITY AND THEIR IMPLEMENTATION IN THE EDUCATIONAL ENVIRONMENT OF THE INSTITUTION OF HIGHER EDUCATION - Anzhelika S. Lesyk; Dmytro Ye. Kornieiev (Alfred Nobel University Publisher, 2021)
The problem of providing multicultural education at higher education institutions is considered. The aim of the article is to analyze the mechanisms of realization of multicultural ideas in the educational environment of a higher education institution. The study reveals the essence of multicultural education, educational environment, multicultural educational environment of higher education. Emphasis is placed on the benefits of multicultural education: increasing productivity, promoting cognitive and moral growth, improving creative problem-solving skills through different points of view, creating positive relationships, reducing stereotypes and prejudices through direct contact and interaction between different people, renewing the viability of society through the richness of different cultures of its members. An analysis is made of the scientific and pedagogical literature, which highlights the results of research on certain aspects of multiculturalism as the basis of higher education. The multicultural educational environment of a higher education institution is defined as a spiritually rich atmosphere of business and interpersonal contacts, which determines the worldview, style of thinking and behavior of the subjects involved and stimulates their need to join national and universal spiritual values. The peculiarities of activities of Ukrainian and foreign institutions of higher education, which promote the development of multicultural education of student youth, are investigated. The peculiarities of realization of ideas of creation of multicultural educational environment in institutions of higher education of the following countries are revealed: Ukraine, the USA, Canada, Belarus, Russia. The most important conditions for the implementation of multicultural education at higher education institutions are: ensuring the multicultural potential of individual disciplines (multicultural-oriented educational programs of educational components), creating a mobile model of multicultural educational environment of higher education (multicultural internal) and multicultural environment (bank of requirements of employers of different countries, training standards, etc.)), the formation of intercultural competencies and intercultural tolerance of students in extracurricular activities, the creation of multicultural classes that cover diversity and include ideas, beliefs or people from different countries and cultures.